Progressive Muscle Relaxation Combined with Lavender Aromatherapy: A Nursing Approach to Blood Pressure Control in Elderly - Diana Permatasari, Eka; Rakhman, Arif; Sukma Riyanti, Asih (Jurnal Berita Ilmu Keperawatan, 2026)
Hypertension remains a common health problem in the elderly and often requires additional non-pharmacological interventions in addition to pharmacological treatment. This study aims to be able to evaluate the effect of progressive muscle relaxation combined with lavender aromatherapy on systolic and diastolic blood pressure in the elderly with hypertension. This quantitative research uses a pre-experimental design of one pretest-posttest group. The target population consists of elderly people with hypertension who live in Balapulang Wetan Village, Indonesia. A total of 23 participants were selected as research samples through proportional random sampling in all environmental units or RWs. All selected participants underwent progressive muscle relaxation exercises with a combination of lavender aromatherapy, performed once a day for three consecutive days. Lavender essential oil with 15 drops dissolved in 30 mL of water is given using a diffuser at each session. Blood pressure was measured before and after the intervention using a digital sphygmomanometer. Data was analyzed with a pair of sample t-tests. The results of the study indicate a statistically significant decrease in systolic and diastolic blood pressure after the intervention or p < 0.05. The combination of progressive muscle relaxation and lavender aromatherapy has been proven to reduce blood pressure in the elderly with hypertension and can be used as an effective non-pharmacological nursing intervention.